Management of Warm Compresses in Typhoid Fever Children - Zaitun, Zaitun; Yuliani S, Ayu; Ameliya, Feni (Jurnal Medisci, 2024)
School-age children are easily targeted for various diseases, especially gastrointestinal diseases because school-age children have not paid much attention to their health, including the snacks they eat. Digestive diseases that most often infect school-age children due to poor schoolchildren's snacks include typhoid fever. Typhoid fever is a disease caused by Salmonella Thypi bacteria. The priority of treatment in typhoid fever patients is hyperthermia management with the application of warm compresses that can help lower the body temperature of patients with typhoid fever. Purpose: From this case study, it is to help reduce body temperature against hyperthermy in school-age children with a medical diagnosis of typhoid fever at Arjawinangun Hospital Cirebon. Method: This scientific paper uses a descriptive qualitative design with the number of subjects as many as 2 respondents of school-age children with a medical diagnosis of typhoid fever who were given an intervention, namely a warm compress. Data collection techniques use interviews, observations and documentation studies. Conclusion: after the cooperative action, one experienced a temperature decrease of 1.1°C from 37.8°C to 36.7°C while patient 2 experienced a temperature decrease of 1.7°C from 38.3°C to 36.6°C. Suggestion: the patient's family can perform the very conflict act independently that has been taught by the nurse and in accordance with the standard operating instructions for warm compress procedures in the manual.